Pemanfaatan Air Hutan Oleh Desa Penyangga di Taman Nasional Bali Barat - Diah Gayatri Sudibya; Ni Gusti Ketut Sri Astiti,; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2023)
Water is one of the most important elements in human life. Water resources are the most valuable gift from God Almighty because they provide benefits in realizing prosperity for the entire community. No one can deny that water is a basic need for all life, whether human, animal or plant, which cannot be replaced by other substances. So it must receive special attention because it involves not only human life but also other creatures, especially if we are talking within the scope of natural resource conservation, which in this case is a National Park. All parties involved in the management of the National Park as a conservation area must have a systematic effort in managing the area which is carried out by planning, protecting, monitoring, controlling, and utilizing which is carried out without destroying the landscape and changing the function of the area. management and utilization of existing water resources in the national park area, especially those used by buffer villages. The results obtained are the problem of using zones that are not in accordance with the established zoning and to overcome this, it is necessary to change the zoning from the core zone to the utilization zone so that the utilization of ground water in the core zone can be utilized as well as possible.